Growth and fecundity of Spodoptera frugiperda on native Zea mays and the teosinte Z. luxurians, from Oaxaca, Mexico - Padilla-Cortes, Erika; Martínez-Martínez, Laura; Chávez-Servia, José Luis (Revista Colombiana de Entomología, 2022)
Resistance to Spodoptera frugiperda (Lepidoptera: Noctuidae) damage has been documented in some Mexican maize races and teosintes. There are approximately 31 races of native maize and three races of teosinte in Oaxaca state, but little is known about their resistance to insect damage. This study compared the development and fecundity of S. frugiperda fed on native maize and the teosinte Zea luxurians, from Oaxaca, Mexico. No significant differences were determined in the development parameters of males and females according to the host plant types, except the pupal weight of males, which was higher on teosinte (0.189 g) than on native maize (0.174 g). Duration from hatching to adult emergence was 28.96 to 30.17 d on native maize and 28.51 to 30.34 d on teosinte. Females emerged before males in both host plant types. The sex ratio was approximately 0.5 for both sexes. Larval weight was higher on teosinte (0.451 to 0.459 g) than on native maize (0.442 to 0.454 g). According to the fecundity parameters, no significant differences in the duration of oviposition, the number of eggs per egg mass, eggs per female, and eggs per host plant types were determined. Fitness Index was positively correlated with the pupal weight of both sexes and the fecundity parameters of S. frugiperda females. Our results demonstrated that larval feeding on native maize and teosinte did not affect the development parameters and fecundity of S. frugiperda. Constitutive defenses in native maize leaves were similar to those of teosinte.